Characteristics Fluid Rumen From Ration With Ratio Rumen Degradable And Ungradable Protein Which Different In-Vitro - Rica Mega Sari; Restu Julia Sari; Dara Surtina (Department of Agriculture, 2022)
The Study aimed to get formulation ration with ratio RDP and The best RUP from a combination of forage feed (field grass, titonia and sweet potato leaves) and concentrate (dregs know, sweet potato wood, and bran) for characteristics condition fluid rumen. A random block design with three (3) treatments and five (5) groups was used in this research. The treatment were enhancement ratio RDP and RUP in ration where P1= 50:50, P2= 55:45, P3= 60:40. The result of the research showed that ratio RDP and RUP which use forage (grass field, titonia and leaf sweet potato sweet) and concentrate (dregs know, sweet potato wood and bran) gave a very significantly different effect (P<0.01) on VFA, and which was not significantly different with respect to pH and NH3. Where the pH and NH3 values are at condition normal and VFA highest on P2 (55:45) aim to get formulation ration with ratio RDP and The best RUP from a combination of forage feed (field grass, titonia and sweet potato leaves) and concentrate (dregs know, sweet potato wood and bran) for characteristics condition fluid rumen. Study this use design Random Group with three (3) treatment and five group. Treatment is enhancement ratio RDP and RUP in ration where P1= 50:50, P2= 55:45, P3= 60:40. If results analysis diversity show existence significant difference between treatments then continued with the DNMRT test. Research result show that ratio RDP and RUP which use forage (grass field, titonia and leaf sweet potato sweet) and concentrate (dregs know, sweet potato wood and bran) gave a very significantly different effect (P<0.01) on VFA, and which was not significantly different with respect to pH and NH3. Where the pH and NH3 values are at condition normal and VFA highest on P2 (55:45)